2009
DOI: 10.1002/bip.21195
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of ulvan: A polysaccharide from green seaweeds

Abstract: Ultrastructural analysis of the gel forming green seaweed sulfated polysaccharide ulvan revealed a spherical-based morphology (10-18 nm diameter) more or less aggregated in aqueous solution. At pH 13 in TBAOH (tetrabutyl ammonium hydroxyde) or NaOH, ulvan formed an open gel-like structure or a continuous film by fusion or coalescence of bead-like structures, while in acidic pH conditions, ulvan appeared as dispersed beads. Low concentrations of sodium chloride, copper or boric acid induced the formation of agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(108 citation statements)
references
References 34 publications
4
100
0
4
Order By: Relevance
“…Manose and galactose also have been found in ulvans from some Ulva species (Lahaye & Robic, 2007). These sugars are structurally grouped by two main repeating disaccharides, which are: the ulvabiuronic acid type A (β-DGlcA (1→4) α-L-Rha 3S →1) and type B (α-L-IdoA (1→4) α-L-Rha 3S →1) (Figure 1) (Paulert et al, 2007;Robic et al, 2009). However, the polysaccharide composition can be more complex and is influenced by taxonomical and/or ecophysiological variations (Lahaye & Robic, 2007).…”
Section: Ulvansmentioning
confidence: 99%
“…Manose and galactose also have been found in ulvans from some Ulva species (Lahaye & Robic, 2007). These sugars are structurally grouped by two main repeating disaccharides, which are: the ulvabiuronic acid type A (β-DGlcA (1→4) α-L-Rha 3S →1) and type B (α-L-IdoA (1→4) α-L-Rha 3S →1) (Figure 1) (Paulert et al, 2007;Robic et al, 2009). However, the polysaccharide composition can be more complex and is influenced by taxonomical and/or ecophysiological variations (Lahaye & Robic, 2007).…”
Section: Ulvansmentioning
confidence: 99%
“…Ulvan represents a class of sulphated heteropolysaccharide extracted from the cell wall of green seaweeds belonging to Ulva sp. whose composition has been extensively debated (Lahaye & Robic, 2007;Robic et al, 2009;) and showed to vary according to several factors including the period of collection, the ecophysiological growth conditions, the taxonomic origins and the post-collection treatment of the algal sources (Lahaye & Robic, 2007). Four types of polysaccharides are reported to be contained in the biomass of Ulva sp., including the water soluble Ulvan and insoluble cellulose as major one and an alkali-soluble linear xyloglucan and glucuronan in minor amounts (Lahaye & Robic, 2007).…”
Section: Ulvan Propertiesmentioning
confidence: 99%
“…The yield of extraction usually ranges from 8% to 29% of the algal dry weight depending on the applied purification procedure (Lahaye & Axelos, 1993;Lahaye et al, 1994). The sugar composition of Ulvan is extremely variable but rhamnose, xylose, glucuronic and iduronic acid and the presence of sulphate g r o u p s h a v e b e e n i d e n t i f i e d a s t h e m a i n constituents of the polymer (Paradossi et al, 2002;Robic et al, 2009). These monomers are arranged in an essentially linear fashion even though a slight degree of branching has been found (Lahaye & Robic, 2007).…”
Section: Ulvan Propertiesmentioning
confidence: 99%
“…Ulvano son polisacáridos solubles en agua extraídos de las paredes celulares de las algas verdes, principalmente de especies pertenecientes al complejo UlvaEnteromorpha (Lahaye & Robic 2007, Robic et al 2009). Está compuesto principalmente de ramnosa, ácidos glucurónico e idurónico y xilosa, encontrándose la mayoría de las veces distribuido en unidades repetidas de disacáridos (Robic et al 2009).…”
Section: Caracteristicas Del Ulvanounclassified
“…Está compuesto principalmente de ramnosa, ácidos glucurónico e idurónico y xilosa, encontrándose la mayoría de las veces distribuido en unidades repetidas de disacáridos (Robic et al 2009). …”
Section: Caracteristicas Del Ulvanounclassified